Features of Indonesian-English with Special Reference to Gorontalese - Hamzah, Aryati; Tahir, Ismail (Eastasouth Institute, 2025)
Language serves as a communication tool. It is made up of signs and symbols. Depending on the nations in which it is utilized, it exhibits different patterns. Language has a critical role in sustaining our social lives in this age of globalization. In Indonesia, English is the foreign language that is typically taught in schools. Because Indonesia is home to many different ethnic groups and languages, the primary language spoken there is a local language known as the mother tongue. As a unifying language, Indonesian is the second language. As an international language, English has also been learned in every region. Furthermore, English is not flawless due to the significant influence of regional or dialectal languages on pronunciation. Students at Gorontalo also study English as a side subject. The author applies the method to finish this article in a way that is scientific. The research's methodology and data analysis technique demonstrate how data is retrieved and examined. Both library research and field research were the methods and techniques the author employed to gather and analyze data for this aim. Following an analysis of the research on Indonesian-English characteristics among Gorontalo people, the author discovers that the Gorontalo people have a habit of saying things like